Strengthening Moderation Be Religious Interfaith Youth in the Religious Moderation Village Assisted by STAKPN Sentani - Siahaan, Daniel Syafaat; Malatuny, Yakob Godlif; Labobar, Yohanes Kristian; Warwer, Fredrik (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
In Hinekombe Village, religious diversity encourages efforts to strengthen religious moderation among youth across faiths. Community service activities focus on strengthening religious moderation for interfaith youth in the Religious Moderation Village assisted by STAKPN Sentani, which aims to increase understanding and practice of religious moderation in order to create social harmony. The methods used in this activity are lectures, interactive discussions, and questions and answers involving youth from various religious backgrounds. In addition, a community-based approach is implemented by encouraging active youth participation in various social activities and interfaith dialogue. Evaluation is carried out through measuring participants' understanding before and after the activity, as well as observing the impact of the program in daily life. The results of the activity showed that the interfaith youth involved experienced an increased understanding of the importance of religious moderation and had a stronger commitment to implementing the values of tolerance and togetherness. Collaboration with the government, religious leaders and educational institutions plays an important role in supporting the sustainability of this program. In conclusion, this PkM succeeded in having a positive impact on interfaith youth in the Religious Moderation Village. With sustainable activities, it is hoped that a more inclusive and harmonious environment will be created in social life.